1991
DOI: 10.1111/j.1476-5381.1991.tb09823.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin antagonists and capsaicin‐induced contraction of the rat isolated urinary bladder: evidence for tachykinin‐mediated cotransmission

Abstract: 1 The possible involvement of tachykinins (TKs) in the contraction produced by capsaicin in the rat isolated urinary bladder was addressed on the hypothesis that co-release of substance P (SP) and neurokinin A (NKA) occurs from sensory nerve terminals. 2 A low concentration of SP (30 nM) produced a rapid contraction which faded to baseline within 10min. A low concentration of NKA (10nM) produced a slowly developing contraction which was still evident at 10min. Capsaicin (1 pM) produced a rapid phasic response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 49 publications
4
31
1
Order By: Relevance
“…Furthermore, in agreement with previous observations, these contractions were caused by a direct action on the muscle, as they were unaffected by tetrodotoxin [6,17]. Tachykinin-induced contractions were also unaffected by peptidase inhibitors, indicating little involvement of enzyme degradation in limiting the action of tachykinins in rat urinary bladder.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, in agreement with previous observations, these contractions were caused by a direct action on the muscle, as they were unaffected by tetrodotoxin [6,17]. Tachykinin-induced contractions were also unaffected by peptidase inhibitors, indicating little involvement of enzyme degradation in limiting the action of tachykinins in rat urinary bladder.…”
Section: Discussionsupporting
confidence: 77%
“…In the rat urinary bladder, the contractile responses to tachykinins are mediated via activation of NK 1 receptors by substance P and NK 2 receptors by neurokinin A [6,7] implying a duplication in tachykinergic signalling. Once released from afferent nerves, the activity of tachykinins at their receptors can be modulated by peptidases.…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S itself undergoes a complete tachyphylaxis, a second administration of this drug being totally ineffective; (2) preparations pretreated with H 2 S (30 mM-3 mM) become less responsive to capsaicin, showing that a (partial) cross-desensitization phenomenon occurs between the two drugs; (3) a combination of tachykinin NK 2 (nepadutant) and NK 1 (GR 82334) receptorselective antagonists, administered at concentrations producing strong, albeit selective, inhibition of responses mediated by these two receptors (Meini et al, 1994), completely prevents H 2 S-induced contractile effects. In a previous study (Maggi et al, 1991), we had shown that less potent and selective NK 1 and NK 2 antagonists (i.e. spantide and L 659877, respectively) are capable of strongly reducing the response to capsaicin in the rat urinary bladder.…”
Section: Resultsmentioning
confidence: 93%
“…The ability of capsaicin to produce smooth muscle excitatory and/or inhibitory effects by activating the local efferent function of capsaicin-sensitive sensory nerves has widely been investigated by our and other groups (Holzer, 1991;Maggi, 1995, for reviews). In particular, in the rat urinary bladder capsaicin produces excitatory motor responses that are mediated by tachykinins (mainly substance P, and neurokinin A) released from the activated sensory nerve terminals (Maggi et al, 1991). Tachykinins, in turn, stimulate tachykinin NK 1 and NK 2 receptors present on detrusor smooth muscle cells to produce the observed contractile response to capsaicin (Maggi et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation